2. 1) 9 + х = 5
х = 5 - 9
х = -4
2) -33 - у = -19
-у = -19 + 33
-у = 14
у = -14
3. 1) -42 + 75 + (-14) + (-26) + 56 = -42 + 75 - 14 - 26 + 56 = 49
2) 12 + (-20) - (-11) - (-6) - 10 = 12 - 20 + 11 + 6 - 10 = -1
3) 3
- (-1
) + (-4
) = 3
+ 1
- 4
= 3
+ 1
- 4
= 4
- 4
= 4
- 4
= 4
- 4
= ![\frac{3}{8} \frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
4. -13,24 + б + 4,9 + 8,24 + (-4,9) = -13,24 + 8,24 + б = -5 + б
если б = 3
:
- 5 + 3
= 3
- 5 = -1![\frac{5}{9} \frac{5}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B9%7D)
5. 1) -5,34 - (-12,14) = -5,34 + 12,14 - больше чем 0
-5,34 - 12,14 - меньше чем 0
-5,34 - (-12,14) ≥ -5,34 - 12,14
2) -176 - 35 - меньше чем 0
-19 + 21 - больше чем 0
-176 - 35 ≤ -19 + 21
6. между -27 и 25 есть 27 + 25 = 52 число и 0
сумма 1 и -1 равна 0, сумма 20 и -20 тоже равна 0, поэтому мы убираем все числа от 1 до 25, остается -26 - 27 = -53
7 не понимаю как делать